2022
DOI: 10.1097/md.0000000000029212
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the application of virtual reality to improve balance, gait and motor function in patients with Parkinson’s disease

Abstract: Background: Virtual reality (VR) is an advanced technique used in physical rehabilitation of neurological disorders, however the effects of VR on balance, gait, and motor function in people with Parkinson's (PD) are still debated. Therefore, the systematic review aimed to determine the role of VR on motor function, balance and gait in PD patients.Methods: A comprehensive search to identify similar randomised controlled trials was conducted targeting 5 databases including Web of Science, PubMed, CINHAL, Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…Moreover, Mandera [ 72 ] shared the opinion that virtual reality can be a supportive therapy for patients with MCI and various forms of dementia to improve adherence to cognitive training of older adults with cognitive impairment. This opinion is coherent with the outcome of the meta-analysis prepared by Kashif et al [ 73 ]. Out of nine studies on motor function, six reported equal improvements in motor function compared to other groups.…”
Section: Further Researchsupporting
confidence: 86%
“…Moreover, Mandera [ 72 ] shared the opinion that virtual reality can be a supportive therapy for patients with MCI and various forms of dementia to improve adherence to cognitive training of older adults with cognitive impairment. This opinion is coherent with the outcome of the meta-analysis prepared by Kashif et al [ 73 ]. Out of nine studies on motor function, six reported equal improvements in motor function compared to other groups.…”
Section: Further Researchsupporting
confidence: 86%
“…Moreover, Mandera [72] shared the opinion that Virtual Reality can be a supportive therapy for patients with MCI and various forms of dementia to improve adherence to cognitive training of older adults with cognitive impairment. This opinion is coherent with the outcome of the meta-analysis prepared by Kashif et al [86]. Out of 9 studies on motor function, 6 reported equal improvement of motor function as compared to other groups.…”
Section: Figuresupporting
confidence: 84%
“…42 Some studies used VR to interact three-dimensional virtual environment. 4,25,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] We also found studies using Robotic-assisted gait training for PD. 24,29,[59][60][61][62] We analyzed several types of AP and categorized them into commercial and non-commercial devices available for research, rehabilitation, or home-based care.…”
Section: Resultsmentioning
confidence: 69%
“…52 Finally, VR rehabilitation should be offered to PD patients as a supplementary approach to existing proven and safe interventions until further and more robust evidence is available. 50,51,53,57 Hence, large trials with good methodologic designs are necessary with a focus on comparing the efficacy of VRbased rehabilitation with conventional treatments and or new emerging technologies.…”
Section: Virtual Realitymentioning
confidence: 99%